Investigating Schizocarp morphology as a taxonomic tool in study of Apiaceae family by utilizing LM and SEM techniques. Issue 7 (9th March 2019) - Kalsoom, Nomana; Zafar, Muhammad; Ahmad, Mushtaq; Sultana, Shazia; Usma, Anwer; Jabeen, Asma
Abstract: In present study, the schizocarp morphology of 14 species belonging to Apiaceae family has been investigated. Light microscopy (LM) and scanning electron microscopy (SEM) have been utilized to highlight qualitative and quantitative features of studied species. Variations have been observed in macro‐ and micro‐morphological features such as color, shape, symmetry, length, width, apex, epicuticular projections, surface patterns, anticlinal, and periclinal wall patterns. Schizocarp shapes observed were oval, round, triangular, linear, elliptic, and globose. Fruit was either homomorphic or heteromorphic. Crystalloids, stellate hair, multicellular spines, and platelets were mostly observed epicuticular projections. Surface patterns on the fruit surface were striate, rugulate‐striate, reticulate, and striato‐knotted. Both macro‐ and micro‐morphological characters can serve as an important tool in classifying Apiaceae family at various taxonomic ranks. Substantial variations observed can assist as useful constraints at various taxonomic levels as they provide reliable and constant details. Disparities observed in schizocarp features can pave a path for Apiaceae family classification based on phylogenetic and molecular studies. Abstract :